Literatur Review : Jus Kurma sebagai Booster Haemoglobin (Hb), Pencegah Anemia pada Remaja Putri. - Aminah Mu'min; Rita Rita (Akademi Kebidanan La Tansa Mashiro, 2022)
Anemia is a condition in the body where hemoglobin (Hb) levels in the blood are lower than normal. Dates or in Latin referred to as phoenix dactylifera provide many benefits for the body. One of the benefits given by dates can prevent anemia because it is rich in calcium and iron, which are two important elements for the formation of blood and spinal cord. The purpose of making this innovation is to make Hb Booster (Dates Juice) for the Prevention of Young Women Anemia. This innovation uses entrepreneurship. After making Hb Booster (Dates Juice) for Prevention of Anemia Adolescent girls all among young women like to drink Hb Booster (date juice) because it tastes good, fresh and up to date when drinking Hb Booster (Dates Juice) for them this is a snack very beneficial for them as well as a lot of nutritional content and enough of the daily needs of adolescents makes them interested in drinking it and the benefits are numerous. Suggestions for adolescents are expected to make efforts to prevent anemia by increasing knowledge about anemia and dates.